Pengaruh Debt to Equity Ratio, Firm Size dan Working Capital terhadap Return on Asset pada Perusahaan Property and Real Estate yang terdaftar di Bursa Efek Indonesia - Diana Felicia; Sherlyn Margareth; Rani Rani; Enda Noviyanti Simorangkir (Politeknik Ganesha Medan, 2020)
This study aims to determine if the independent variables affects dependent variable on Property and Real Estate companies on the Indonesia Stock Exchange from January to December in the period of 2015-2017. Where the independent variables are Debt to Equity Ratio, Firm Size and Working Capital. Whereas, the dependent variable is Return on Asset. Where there are as many as 46 Property and Real Estate companies listed on the Indonesia Stock Exchange. However, the samples are examined only 35 companies in accordance with the desired criteria. This research method uses multiple linear regression analyses with the aid of SPSS 19. The results of this analysis shows in the period of 2015-2017 there is a Property and Real Estate company that on the T test Debt to Equity Ratio is partially no effect on Return On Asset, Firm Size in partial no significant effect on Return on Asset and Working Capital also partial no significant effect on Return on Asset. However, on the F test Debt to Equity Ratio, Firm Size and Working Capital simultaneously have significant effect on Return on Asset. Adjusted R Square at 0,110 or 11% which means that 11% variable Return on Asset were influenced by Debt to Equity Ratio, Firm Size and Working Capital while (100%-11%) 89% of its unexplained variable.